Production of Plant-Derived Oleuropein Aglycone by a Combined Membrane Process and Evaluation of Its Breast Anticancer Properties - Mazzei, Rosalinda; Piacentini, Emma; Nardi, Monica; Poerio, Teresa; Bazzarelli, Fabio; Procopio, Antonio; Di Gioia, Maria Luisa; Rizza, Pietro; Ceraldi, Rosangela; Morelli, Catia; Giorno, Lidietta; Pellegrino, Michele (Frontiers in Bioengineering and Biotechnology, 2020)
Natural products and herbal therapies represent a thriving field of research, but methods for the production of plant-derived compounds with a significative biological activity by synthetic methods are required. Conventional commercial production by chemical synthesis or solvent extraction is not yet sustainable and economical because toxic solvents are used, the process involves many steps, and there is generally a low amount of the product produced, which is often mixed with other or similar by-products. For this reason, alternative, sustainable, greener, and more efficient processes are required. Membrane processes are recognized worldwide as green technologies since they promote waste minimization, material diversity, efficient separation, energy saving, process intensification, and integration. This article describes the production, characterization, and utilization of bioactive compounds derived from renewable waste material (olive leaves) as drug candidates in breast cancer (BC) treatment. In particular, an integrated membrane process [composed by a membrane bioreactor (MBR) and a membrane emulsification (ME) system] was developed to produce a purified non-commercially available phytotherapic compound: the oleuropein aglycone (OLA). This method achieves a 93% conversion of the substrate (oleuropein) and enables the extraction of the compound of interest with 90% efficiency in sustainable conditions. The bioderived compound exercised pro-apoptotic and antiproliferative activities against MDA-MB-231 and Tamoxifen-resistant MCF-7 (MCF-7/TR) cells, suggesting it as a potential agent for the treatment of breast cancer including hormonal resistance therapies.